This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Garcia, Ilse – Exam 2 – Due: Oct 31 2007, 1:00 am – Inst: Fonken 1 This printout should have 20 questions. Multiplechoice questions may continue on the next column or page – find all choices before answering. The due time is Central time. 001 (part 1 of 1) 10 points Find f ( x ) when f ( x ) = ‡ x 1 x + 1 · 2 . 1. f ( x ) = 6( x + 1) ( x 1) 3 2. f ( x ) = 4( x 2) ( x + 1) 3 3. f ( x ) = 6( x 2) ( x + 1) 3 4. f ( x ) = 4( x + 1) ( x 1) 3 5. f ( x ) = 4( x 1) ( x + 1) 3 correct 6. f ( x ) = 6( x + 2) ( x 1) 3 Explanation: By the Chain and Quotient Rules, f ( x ) = 2 ‡ x 1 x + 1 · ( x + 1) ( x 1) ( x + 1) 2 . Consequently, f ( x ) = 4( x 1) ( x + 1) 3 . keywords: derivative, quotient rule, chain rule 002 (part 1 of 1) 10 points Determine f ( x ) when f ( x ) = 2 √ x sin √ x . 1. f ( x ) = 2 n cos √ x √ x sin √ x o 2. f ( x ) = 1 2 n cos √ x √ x sin √ x o 3. f ( x ) = cos √ x √ x sin √ x 4. f ( x ) = 1 2 n sin √ x √ x + cos √ x o 5. f ( x ) = 2 n sin √ x √ x + cos √ x o 6. f ( x ) = sin √ x √ x + cos √ x correct Explanation: By the Chain and Product Rules, f ( x ) = 2 2 √ x sin √ x + 2 √ x 2 √ x cos √ x . Consequently, f ( x ) = sin √ x √ x + cos √ x . keywords: chain rule, product rule, trig func tion 003 (part 1 of 1) 10 points Find the second derivative of f when f ( x ) = cos2 x + 3sin 2 x . 1. f 00 ( x ) = cos2 x 2. f 00 ( x ) = cos2 x 3. f 00 ( x ) = 2cos2 x 4. f 00 ( x ) = sin2 x 5. f 00 ( x ) = 2cos2 x correct Garcia, Ilse – Exam 2 – Due: Oct 31 2007, 1:00 am – Inst: Fonken 2 6. f 00 ( x ) = 2sin2 x Explanation: Differentiating once we see that f ( x ) = 2sin2 x + 6sin x cos x . Now 2sin x cos x = sin2 x , so f ( x ) = sin2 x . Consequently, by differentiating once again we obtain f 00 ( x ) = 2cos2 x . keywords: second derivative, trig function 004 (part 1 of 1) 10 points Determine the third derivative, f 000 ( x ), of f when f ( x ) = √ 2 x + 1 . 1. f 000 ( x ) = (2 x + 1) 3 / 2 2. f 000 ( x ) = 3(2 x + 1) 5 / 2 3. f 000 ( x ) = (2 x + 1) 5 / 2 4. f 000 ( x ) = 3(2 x + 1) 5 / 2 correct 5. f 000 ( x ) = 3(2 x + 1) 3 / 2 6. f 000 ( x ) = (2 x + 1) 3 / 2 Explanation: TousetheChainRulesuccessively it’smore convenient to write f ( x ) = √ 2 x + 1 = (2 x + 1) 1 / 2 . For then f ( x ) = 1 2 · 2 · (2 x + 1) 1 / 2 = (2 x + 1) 1 / 2 , while f 00 ( x ) = 1 2 · 2 · (2 x + 1) 3 / 2 = (2 x + 1) 3 / 2 , and f 000 ( x ) = 3 2 · 2 · (2 x + 1) 5 / 2 . Consequently, f 000 ( x ) = 3(2 x + 1) 5 / 2 . keywords: third derivative, chain rule 005 (part 1 of 1) 10 points Find dy/dx when 5 x 2 + 3 y 2 = 9 . 1. dy dx = 5 x 3 y 2. dy dx = 3 xy 3. dy dx = 5 x y 4....
View
Full
Document
This note was uploaded on 02/22/2009 for the course M 58365 taught by Professor Gilbert during the Spring '08 term at University of Texas at Austin.
 Spring '08
 Gilbert
 Calculus

Click to edit the document details